Product Development, Nutritional Characteristics and Consumers Acceptability Studies of Doughnut Partially Substituted with Carrot (Daucus carota) and Mango (Mangifera indica L) Flour Fortified with Date (Phoenix dactylifera L) Fruits Syrup as Sweetener - Elechi, Jasper O.G (Food and Applied Bioscience Journal, 2022)
A monotonous diet, bad eating habits, and micronutrient deficiencies that typically accompany food-related illnesses are all linked to a heavy reliance on a few primary crops. Food and nutrition security may be achieved by eating a diversified healthy diet that emphasizes cheap, nutrient-dense plant-based foods such fruits, vegetables, whole grains, and legumes. The goal of this study was to use mango and carrot powder to partially replaced wheat flour and in combination with date syrup in a sugar-free doughnut recipe to increase the health-promoting characteristics of doughnut. For consumer-acceptable doughnuts, product design was utilized to identify the proper quantity of mango and carrot powders, as well as date syrup. The doughnut was tested for its physical characteristics, proximate composition, micronutrient contents, and consumer acceptability. The findings of the physical study revealed that the values of Carrot flour (CF), Mango pulp flour (MPF), and Date-Syrup (DS) replacement had a significant (p<0.05) impact on the weight, volume, and specific volume. The chemical analysis revealed an increased proportion of fibre (1.62-5.20%), fat (25.50-34.67%), calorie content (372.48-451.55%), β-carotene (33.50-69.30µg/100g), as well as a decreased in protein (13.13-7.40%) and moisture (33.89-21.63%) in doughnuts substituted with MPF, CF, and DS. Calcium (21.63-43.24mg/100g), Iron (4.87-8.90 mg/100g), Potassium (176.10-236.14 mg/100g), and Phosphorus (200.30-280 mg/100g) all exhibited a substantial increase in minerals. The quantity of CF, MPF, and DS added to the doughnut caused the crust and crumb to shift from a light to a darker hue, which was connected with the amount of CF, MPF, and DS added. Overall acceptance was significantly (p<0.05) highest for doughnuts made with 25% CF, 25% MPF, and 25% DS (7.63) and significantly (p<0.05) from the control. The study found that improving the selection of one or more components can be a useful method for improving the health benefits of snack foods without sacrificing sensory qualities.